2018
DOI: 10.1007/s10068-018-0429-7
|View full text |Cite
|
Sign up to set email alerts
|

Textural character of sweet potato root of Korean cultivars in relation to chemical constituents and their properties

Abstract: A relationship between chemical constituents and physicochemical and textural properties of different Korean sweet potato (SP) cultivars were investigated in terms of the hardness of raw and cooked root, alcohol insoluble solid (AIS), starch and amylose content, amylase activities, and pasting properties. Correlation coefficients were analyzed and principal component analysis was performed. The hardness of cooked root was found to correlate with the hardness ratio of cooked/raw SP, AIS content (0.75**), starch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…(2011), Yoon et al. (2018), and Lee and Lee (2017) were analyzed by flesh color (combined with this study's data and separately), again, the starch from OFSP was lower than yellow/cream/white‐fleshed sweetpotatoes (Figures 4b and 4c). This difference in pasting temperatures may be due to biochemical differences in OFSP versus yellow/cream/white‐fleshed sweetpotatoes.…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations
“…(2011), Yoon et al. (2018), and Lee and Lee (2017) were analyzed by flesh color (combined with this study's data and separately), again, the starch from OFSP was lower than yellow/cream/white‐fleshed sweetpotatoes (Figures 4b and 4c). This difference in pasting temperatures may be due to biochemical differences in OFSP versus yellow/cream/white‐fleshed sweetpotatoes.…”
Section: Resultsmentioning
confidence: 56%
“…Student's t ‐tests (α = 0.05) and quantiles of sweetpotato starch pasting temperature averages grouped by sweetpotato flesh color from this study (a); Yoon et al. (2018), Waramboi et al. (2011), and Lee and Lee (2017) (b); and combined data from this study (black dots) and the other studies (gray dots) (c).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…4). Yoon et al 2018 revealed a positive correlation between the hardness of the cooked sweet potato tubers with the starch content (r = 0.64).…”
Section: Peak Force-deformation Of Steamed Tubersmentioning
confidence: 97%